Chaguanas local area plan interim report. - Halcrow Group (Trinidad and Tobago). (Halcrow Group (Trinidad and Tobago)., 2011)
Describes the national development concept, the human and natural environments of the study area, transport and infrastructure, planning strategy, the development of the proposed Chaguanas Town Centre and implementation of the plans.
http://www.nalis.gov.tt/InterimReportChaguanas-.html
Keywords: Physical planning - Land use – Chaguanas, Urban planning, Urban development, Economic development, Natural resource, Socio-economic factors – Chaguanas, Infrastructure. Transportation, Chaguanas.